2011
DOI: 10.1007/s11596-011-0679-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between aberrant methylation of FAS promoter and biological behavior of bladder urothelial carcinoma

Abstract: This study examined the promoter methylation of APO-1/CD95 (Fas) gene in bladder urothelial carcinoma and analyzed the relationship between the Fas promoter methylation and the biological behavior of bladder cancer. Promoter methylation of Fas gene was detected by methylation-specific PCR (MSP) in 4 bladder cancer cell lines, 50 human bladder urothelial carcinoma samples and l0 normal bladder tissue samples. Correlation of the aberrant methylation of Fas promoter with the clinicopathological parameters was sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These data further suggest that gene silencing by DNA hypermethylation and histone deacetylation commonly occur on tumor suppressor and proapoptotic genes. Fas downregulation by DNMT1 accumulation has been observed in osteosarcoma and lung carcinoma cell lines (58), and aberrant methylation of Fas promoter was observed in bladder carcinoma (48,59). It has also been reported that DNMT1 silencing upregulates DR5 expression and sensitizes human hepatoma cells to TRAIL-mediated apoptosis (60) and hypermethylation of the DR4 promoter was noted in invasive gastric carcinoma (61).…”
Section: Discussionmentioning
confidence: 95%
“…These data further suggest that gene silencing by DNA hypermethylation and histone deacetylation commonly occur on tumor suppressor and proapoptotic genes. Fas downregulation by DNMT1 accumulation has been observed in osteosarcoma and lung carcinoma cell lines (58), and aberrant methylation of Fas promoter was observed in bladder carcinoma (48,59). It has also been reported that DNMT1 silencing upregulates DR5 expression and sensitizes human hepatoma cells to TRAIL-mediated apoptosis (60) and hypermethylation of the DR4 promoter was noted in invasive gastric carcinoma (61).…”
Section: Discussionmentioning
confidence: 95%
“…In line our results, Li W et al ., (2011) shown that the rate of FAS promoter methylation in bladder urothelial carcinoma samples is higher than normal samples ( p <0.01) ( 24 ). In addition, a vast literatures have been highlighted the aberrant promoter methylation of FAS gene in different types of cancers including Lymphomas, CXCA, melanoma, Colon, Prostatic and Lung ( 25 - 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The scale, prepared by Li (2008), contains five dimensions: altruistic behavior responsibility, respect and care for others, care and care for oneself, altruistic behavior performance, and selfinterested behavior and concepts. There are a total of 22 items in the scale, and the Likert 7-level score from "very inconsistent" to "very consistent" is adopted.…”
Section: Altruistic Behavior Scalementioning
confidence: 99%